2022
DOI: 10.1155/2022/6081375
|View full text |Cite|
|
Sign up to set email alerts
|

The Construction Path and Protection Measures of Wetland Park from the Perspective of National Participation in the New Era

Abstract: In order to study many problems, such as unreasonable wetland protection, development, and utilization, resulting in a large reduction of wetland area, and so on, with the rise of the construction and research upsurge of the municipal wetland park, a method of wetland park construction path and protection measures based on the perspective of the new era of national participation was proposed. This method takes the construction of urban wetland parks as the research object, starts with the actual demand for wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Third, wetland parks promote the sustainable development of wetlands through the rational utilization of resources. As an illustration, Li and Li [23] observed that wetland parks protect wetland ecosystems by utilizing wetland resources and avoiding unreasonable reductions in wetland areas [24]. Wetland parks are established to protect wetland resources.…”
Section: Wetland Parks Are Necessary For the Protection Of Wetland Ec...mentioning
confidence: 99%
“…Third, wetland parks promote the sustainable development of wetlands through the rational utilization of resources. As an illustration, Li and Li [23] observed that wetland parks protect wetland ecosystems by utilizing wetland resources and avoiding unreasonable reductions in wetland areas [24]. Wetland parks are established to protect wetland resources.…”
Section: Wetland Parks Are Necessary For the Protection Of Wetland Ec...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%